Biological corridors in Costa Rica: methodology formonitoring landscape structure and connectivity - Sandoval Murillo, Luis Fernando (2025)
In recent decades, global change has accelerated environmental deterioration, generating an imbalance in the society-nature relationship and justifying the relevance of ecological conservation. One of the effects of this deterioration is the fragmentation of natural ecosystems, which has led to the establishment of connectivity spaces known as biological corridors. In Costa Rica, CBs are a strategy to reestablish connectivity between protected wild areas, reaching 53 CBs covering 38% of the territory by 2023. Despite their abundance, there is little research that addresses their efficiency, considering that they are key to the conservation of biodiversity and the maintenance of ecosystem services, in addition to mitigating the effects of climate change and improving ecosystem resilience from the perspective of the Sustainable Development Goals. This article proposes a methodology to evaluate fragmentation and connectivity from landscape ecology as a process of monitoring CBs in the country, based on six case studies. This methodology will not only allow the generation of data and identify areas for improvement in the management of CBs, but also constitutes an input for local committees, which are spaces where social and institutional integration are essential for the consolidation of these areas.